Well-Being and Jesus' Healing Ministry in Relation to Healing in African Religion - Dairo, Afolorunso (Asia-Alrica Journal of Mission and Ministry (AAMM), 2012)
T—This paper is premised on the dictum that 'health is wealth'. The issue of well-being is an important matter to all in any society. In the ancient world, health was a highly prized possession, and it is one of the most important considerations occupying our' modern society. The study examines the processes of well-being in the ministry of Jesus and in African traditional religion vis-à-vis. the advancement of medicine in modern civilization. The study discovered various religious views of illness and explored how Africans utilize healing systems and religious practices to address matters of disease and affliction. Moreover, the element of secrecy in African 'religion and its healing practices is an issue that cannot be under-estimated. The paper discusses Jesus' healing ministry exhaustively, and its relation to healing in African Religion. The necessity of the healing ministry to Jesus was highlighted. A multi-dimensional approach is recommended in healing all manners of diseases and enhancing well= being, for all
Keywords: Well-being; Jesus; Healing; Ministry African Religion